2014
DOI: 10.1007/s10725-014-9959-z
|View full text |Cite
|
Sign up to set email alerts
|

Hairy root exudates of allelopathic weed Chenopodium murale L. induce oxidative stress and down-regulate core cell cycle genes in Arabidopsis and wheat seedlings

Abstract: The effects of Chenopodium murale root exudates, applied as phytotoxic medias (PMs), were tested on Arabidopsis thaliana and Triticum aestivum. The effects of PMs, where wild-type roots (K), hairy roots derived from roots (R clones) or from cotyledons (C clones) were cultured, were different. K medium suppressed Arabidopsis germination, while other PMs reduced root and leaf elongation and the number of rosette leaves. R media were more phytotoxic than C media. Treatment of Arabidopsis with R8 downregulated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Rapid increase in H 2 O 2 level after R5 treatment (about 50% higher compared to control) represents the typical reaction to allelochemicals since the similar effect was annotated after application of numerous other allelochemicals (Soltys et al 2011(Soltys et al , 2014Guan et al 2014;Krasuska et al 2016;Andrzejczak et al 2018). Different increments of H 2 O 2 roots and shoots content could be explained by differential activation of enzymatic antioxidant defense system, observed in wheat shoot and root in the previous study (Dmitrović et al 2015a).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Rapid increase in H 2 O 2 level after R5 treatment (about 50% higher compared to control) represents the typical reaction to allelochemicals since the similar effect was annotated after application of numerous other allelochemicals (Soltys et al 2011(Soltys et al , 2014Guan et al 2014;Krasuska et al 2016;Andrzejczak et al 2018). Different increments of H 2 O 2 roots and shoots content could be explained by differential activation of enzymatic antioxidant defense system, observed in wheat shoot and root in the previous study (Dmitrović et al 2015a).…”
Section: Discussionsupporting
confidence: 57%
“…Despite induction of antioxidant enzymatic system, documented previously by Dmitrović et al (2015a), increased TBARS content, in both roots and shoots, suggested that generated ROS molecules could not be eliminated completely. This claim is supported by the results of H 2 O 2 content measurement and ROS imaging, using H 2 DCF-DA probe which also showed increased level of H 2 O 2 and other ROS molecules in tissues of R5 treated plants.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations